2021
DOI: 10.3389/fonc.2020.580276
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Based System Biology Exploration Reveals Homogeneous Tumorigenicity of Alimentary Tract Malignancy

Abstract: Malignancies of alimentary tract include esophageal carcinoma (ESCA), stomach adenocarcinoma (STAD), colon adenocarcinoma (COAD), and rectum adenocarcinoma (READ). Despite of their similarities in cancer development and progression, there are numerous researches concentrating on single tumor but relatively little on their common mechanisms. Our study explored the transcriptomic data of digestive tract cancers from The Cancer Genome Atlas database, yielding their common differentially expressed genes including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…20 In 2021, Lu uncovered the homogeneous tumorigenicity of the alimentary canal, and the SERPINE1/hsa-mir-145/SNHG1 axis was identified as a potential prognostic indicator and the therapeutic target of alimentary canal malignancies via WGCNA using the TCGA database. 21 Compared to multiple analyses of the TCGA STAD cohort via WGCNA, there is an absence of the GEO STAD cohort for WGCNA. In this study, we selected GEO datasets with clinical features, including the STAD stage and grade.…”
Section: Discussionmentioning
confidence: 99%
“…20 In 2021, Lu uncovered the homogeneous tumorigenicity of the alimentary canal, and the SERPINE1/hsa-mir-145/SNHG1 axis was identified as a potential prognostic indicator and the therapeutic target of alimentary canal malignancies via WGCNA using the TCGA database. 21 Compared to multiple analyses of the TCGA STAD cohort via WGCNA, there is an absence of the GEO STAD cohort for WGCNA. In this study, we selected GEO datasets with clinical features, including the STAD stage and grade.…”
Section: Discussionmentioning
confidence: 99%
“…The encoded product of SERPINE1 is plasminogen activator inhibitor 1, which has the effect of inhibiting brinolysis. SERPINE is signi cantly related to the poor prognosis of head and neck cancer, glioma, gastric cancer, and colon cancer (51)(52)(53). In colon cancer, the expression of SERPINE1 is up-regulated, which is related to the aggressiveness of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the microarray data analysis of 875 gastric cancer patients indicated that upregulation of PTGDR2 expression was significantly associated with a better prognosis. Lu et al screened five key genes, including PTGDR2, CXCL3, NPBWR1, TAS2R38, and ADCY6, and their correlation with gastrointestinal tumor grades, related histological types, and patient age was assessed via the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) database [77]. Wang et al studied a cohort of 123 triple-negative breast cancer (TNBC) in addition to gastric cancer and constructed a column plot model using PTGDR2, which predicted the 1-5 year overall survival (OS) rate of these patients.…”
Section: Role Of the Pgd2/ptgdr2 Signaling Pathway In Tumor Expressio...mentioning
confidence: 99%